2013
DOI: 10.4028/www.scientific.net/amr.631-632.265
|View full text |Cite
|
Sign up to set email alerts
|

Similar Constructive Method for Solving the Nonlinear Spherical Percolation Model in Dual-Porosity Media

Abstract: This paper presents a spherical percolation model for dual-porosity media reservoir, where the quadratic-gradient term, wellbore storage and three types of outer boundary conditions: constant pressure boundary, closed boundary and infinity boundary were considered. Then a new method: Similar Constructive Method was put forward for solving this type of percolation model. And solutions of the dimensionless reservoir pressure and the dimensionless bottomhole pressure in Laplace space were obtained. It was proved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…Similar structure of solutions for some second order differential equations had been investigated in references [1][2][3][4][5][6]. The authors [7][8][9][10][11] built mathematical models for some reservoirs such as composite reservoir, homogeneous reservoir and dual porosity reservoir, which can be transformed into BVP in Laplace space and found that their solutions have a unified expression under three different kinds of boundary conditions. Hermit Equation has some applications in several research areas, such as quantum mechanics and fluid mechanics.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Similar structure of solutions for some second order differential equations had been investigated in references [1][2][3][4][5][6]. The authors [7][8][9][10][11] built mathematical models for some reservoirs such as composite reservoir, homogeneous reservoir and dual porosity reservoir, which can be transformed into BVP in Laplace space and found that their solutions have a unified expression under three different kinds of boundary conditions. Hermit Equation has some applications in several research areas, such as quantum mechanics and fluid mechanics.…”
Section: Introductionmentioning
confidence: 93%
“…In recent years, there have been extensive reportings on solutions for boundary value problems (BVP) of differential equation [1][2][3][4][5][6][7][8][9][10][11]. Similar structure of solutions for some second order differential equations had been investigated in references [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [15,16] found that the solutions of the initial-boundary value problems for a class of second-order ODEs have similar structure of continuous fraction; then, they proposed the similar structure theory (SST) and applied it to the seepage model of the oil and gas reservoir [17][18][19]; the similar structure solutions with continued fraction form were also obtained. After years of research, Li et al [20,21] proposed the similar constructive method (SCM), by which the semianalytical solution of the seepage equation can be easily obtained without complicated and trivial derivation. By using the SCM, Dong et al [22] studied how to solve a BVP of three-region composite second-order linear homogeneous ODE; then, they [23] found a simple method for constructing the exact solutions of the nonhomogeneous mixed BVP for sets of n-interval composite second-order ODE with variable coefficients.…”
Section: Introductionmentioning
confidence: 99%
“…SCMS of the boundary value problems of Airy equation, Weber equation, Euler hypergeometric equation, and composite first Weber system were studied [24][25][26][27][28]. SCMS in fractal dual-porosity reservoir and dual-permeability reservoir were presented [29][30][31].…”
Section: Introductionmentioning
confidence: 99%